Tabletop Simulations in Medical Emergencies: A Scoping Review - Frégeau, Amélie; Vinette, Billy; Lapierre, Alexandra; Maheu-Cadotte, Marc-André; Fontaine, Guillaume; Castonguay, Véronique; Flores-Soto, Rodrigo; Garceau-Tremblay, Zoé; Blais, Samuel; Vigneault, Laura-Philippe; Hansen-Jaumard, Delphine; Laramée, François; et al. (Simulation in healthcare : journal of the Society for Medical Simulation, 2025)
Tabletop simulations (TTS) are a novel educational modality used in health care education. The objective of this scoping review was to describe the use of TTS in medical emergencies, specifically settings, specialties, participants, formats, and outcomes.We included 70 studies (33 descriptive studies [47%], 33 cohort studies [47%], and 2 randomized controlled trials [3%]), of which 65 reported positive results regarding reaction and learning educational outcomes (reaction: n = 37, 53%; learning: n = 25, 36%; behavior: n = 7, 10%; result: n = 1, 1%). The scenario for most TTS was a disaster (n = 56; 80%). Most TTS involved participants from several professions (n = 45; 64%). A board game was used in 26 studies (37%).Most studies on TTS in medical emergencies involved participants from multiple professions addressing disaster scenarios and showed positive results pertaining to reaction or learning educational outcomes.